2018
DOI: 10.1186/s40529-018-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Age and site-specific pattern on encrustation of charophytes

Abstract: Encrustation and element content (Ca, Fe, K, Mg and P) of charophytes was studied along plant thalli to investigate the dependency of thallus age and site-specificity. Charophytes were collected from five sampling sites (Angersdorfer Teiche, Asche, Bruchwiesen, Krüselinsee and Lützlower See) which were distinct with respect to water chemistry. Furthermore, photosynthesis was measured to identify the physiological state of plants in habitat waters and with the addition of different ion concentrations (Ca2+, K+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Many studies have addressed charophyte calcification, including its mechanisms (e.g., McConnaughey and Falk 1991; McConnaughey and Whelan 1997; Sand‐Jensen et al 2018, 2021), the composition and amount of encrustation specific to species, thallus age, site and season. They frequently concluded that the encrusted calcium carbonate was finally deposited in lake sediments (e.g., Pukacz et al 2014 a , 2014 b , 2016; Herbst and Schubert 2018; Herbst et al 2018 a , 2018 b ). Our study shows that the fate of summer maximum encrustation is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have addressed charophyte calcification, including its mechanisms (e.g., McConnaughey and Falk 1991; McConnaughey and Whelan 1997; Sand‐Jensen et al 2018, 2021), the composition and amount of encrustation specific to species, thallus age, site and season. They frequently concluded that the encrusted calcium carbonate was finally deposited in lake sediments (e.g., Pukacz et al 2014 a , 2014 b , 2016; Herbst and Schubert 2018; Herbst et al 2018 a , 2018 b ). Our study shows that the fate of summer maximum encrustation is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…The location of isolated Kranz cells in this dicot is not unlike the location of isolated Kranz cells in Arundinella hirta. The isolated Kranz cells of the dicot, as might be expected, are arranged in clusters rather than parallel strands, however, and unlike the Arundinella cells, appear to be always associated with at least some vascular tissue (isolated veinlets), HERBST (1972) reports that these isolated veinleits "consist solely of tracheids, with no associated xylary parenchyma or phloem cells".…”
mentioning
confidence: 83%
“…Before addressing this question, it may be productive to also consider an anatomical aberration in the dicot Euphorbia forbesii, reported to be a C 4 species (KRENZER et al 1975). HERBST (1972) noted that several species of Euphorbia (subspecies Chamaesyce which contains all the known C 4 Euphorbia) were characterized by numerous isolated disjunct veins that were surrounded by large parenchyma cells. Figure 5 is a paradermal view of a Euphorbia [orbesii leaf that was cleared and stained with 1 2K!.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This process has a decalcifying effect on surrounding water and, by precipitation of inorganic phosphorus incorporates this element and carbon into sediments, rendering them relatively inaccessible to biological activity (Murphy, Hall & Yesaki, 1983; Anderson & Ring, 1999; Rodrigo, Alonso‐Guillén & Soulié‐Märsche, 2009). There remains much to be understood about the biochemistry of these mineral encrustations, but they clearly depend on species, age and the ionic concentrations of the environment (Herbst & Schubert, 2018).…”
Section: Introductionmentioning
confidence: 99%